2005
DOI: 10.1055/s-2005-870139
|View full text |Cite
|
Sign up to set email alerts
|

Menin Molecular Interactions: Insights into Normal Functions and Tumorigenesis

Abstract: Multiple endocrine neoplasia type 1 (MEN1) is an autosomal dominant disease predisposed by heterozygous germline mutations in the MEN1 tumor suppressor gene. Biallelic loss of MEN1 resulting from small mutation and/or loss of heterozygosity occurs in a large tissue spectrum of MEN1 tumors or non-hereditary tumors. Mouse models of MEN1 underexpression or overexpression have also supported the tumor-suppressor effect of the MEN1 gene. Menin, the 610-amino-acid protein encoded by MEN1, is expressed ubiquitously a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(76 citation statements)
references
References 44 publications
1
74
0
1
Order By: Relevance
“…The MEN1 gene on chromosome 11q13 includes 10 exons encoding the 610 amino acid menin protein. Menin is ubiquitously expressed and preferentially located in the nucleus, it has more than 40 interacting proteins, and it is involved in a large number of biological functions, such as DNA repair, chromatin modification, transcription, cell division, protein degradation, motility and adhesion (Agarwal et al 2005, Balogh et al 2006. By now, more than 1000 mutations have been recognized (Lemos & Thakker 2008), the majority leading to truncation of the protein.…”
Section: Genetic Syndromesmentioning
confidence: 99%
“…The MEN1 gene on chromosome 11q13 includes 10 exons encoding the 610 amino acid menin protein. Menin is ubiquitously expressed and preferentially located in the nucleus, it has more than 40 interacting proteins, and it is involved in a large number of biological functions, such as DNA repair, chromatin modification, transcription, cell division, protein degradation, motility and adhesion (Agarwal et al 2005, Balogh et al 2006. By now, more than 1000 mutations have been recognized (Lemos & Thakker 2008), the majority leading to truncation of the protein.…”
Section: Genetic Syndromesmentioning
confidence: 99%
“…37 Several tumor suppressor roles of menin have been disclosed so far, such as, a) cell cycle and cell growth control, b) transcription regulation, c) DNA repair, d) genome stability, e) apoptosis regulation, and f) endocrine cell proliferation. 37,38 A MEN1 germline mutation predisposes the genome to a second mutational event concerning MEN1-associated glands, causing loss of heterozygosity (LOH) of the 11q13 locus. The inactivation of menin is predicted to disrupt its tumor suppressor molecular pathways, thus leading to MEN1 tumorigenesis.…”
Section: Genetic Aspects Of Men1mentioning
confidence: 99%
“…Interaction of menin with Smad3 is reported to result in activation of transforming growth factor-h (TGF-h)-induced transcription (8), and the interaction of menin with Smad1, Smad3, Smad5, and Runx2 may participate in the TGF-hmediated and bone morphogenetic protein-2 -mediated pathways of commitment of multipotential mesenchymal stem cells to osteoblast lineage (9)(10)(11). Previous studies of gene expression in tumors, cell lines, and embryos have identified nonoverlapping sets of gene(s), whose expression is affected by menin (5,12,13). A recent report of chromatin immunoprecipitationon-chip analysis has identified thousands of menin-binding promoter targets in the human genome (14).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these are nuclear proteins involved in transcriptional regulation, including JunD, nuclear factor-nB, Pem, the COMPASS-like complex, Smad proteins 1, 3, and 5, RunX2, and histone deacetylases (5). The COMPASS-like complexes include the trithorax proteins mixed lineage leukemia 1/2, which possess histone methyl transferase activity.…”
Section: Introductionmentioning
confidence: 99%